Find the difference quotient and simplify your answer.
f(x) = x2 – 2x + 6,
h = 0
h
f(8 + h) – f(8),
![Find the difference quotient and simplify your answer fx x2 2x 6 h 0 h f8 h f8 class=](https://us-static.z-dn.net/files/d46/d9340c8c6bf3d6e60e8f49cab49e5e19.png)
We're given that
[tex]f(x)=x^2-2x+6[/tex]
which means
[tex]f(x+h)=(x+h)^2-2(x+h)+6=x^2+2xh+h^2-2x-2h+6[/tex]
When we subtract these, several terms cancel:
[tex](x^2+2xh+h^2-2x-2h+6)-(x^2-2x+6)=2xh+h^2-2h[/tex]
So the difference quotient is
[tex]\dfrac{f(x+h)-f(x)}h=\dfrac{2xh+h^2-2h}h[/tex]
and since h ≠ 0, we can cancel it out to end up with
[tex]\dfrac{f(x+h)-f(x)}h=2x+h-2[/tex]
Now plug in x = 8 (this could have been done at any prior point):
[tex]\dfrac{f(8+h)-f(8)}h=14+h[/tex]